Le sujet neurocognitif et l'éducation : un paradoxe ? - Claude Caussidier
The experimental data of cognitive neuroscience make it possible to establish causal bonds between the activity of the cerebral structures and the psychological functions of the individuals, among them the capacities to learn. The implementation of these bonds gave rise to the neuroscience of education (neuroeducation) which goal is the development and the application of programs of educational technologies to help with teaching. Within this framework, learning difficulties are then regarded as dysfunctions of the brain compared to definite biological standards. By using the contributions of educational neuroscience, the teacher could thus become the expert of an education based on scientific results. Then, will recommended teaching be aimed at measurable objectives or will it encourage such goals as "thinking more clearly" or "capacity to discuss"? By which values will be underlain the educational practices validated by scientific results? Consequently, if we want to escape a formatting of our brains, it seems necessary to take into account the subject (in philosophy, the essential nature of the individual as distinguished from its attributes), child or adult, who cognitive neuroscience wishes to educate.